1994
DOI: 10.1007/bf00005727
|View full text |Cite
|
Sign up to set email alerts
|

Empirical evidence of the importance of sediment resuspension in lakes

Abstract: This paper reviews the empirical evidence for bottom sediment resuspension, which has been documented in many aquatic systems, and attempts to put those observations into a predictive framework. The evidence suggests that resuspension is episodic in all systems with the spatial extent of resuspension being determined by the wind speed, duration of disturbance, effective lake fetch and lake morphometry. The rates of deposition of resuspended material vary greatly with measurements recorded between 0.5 and 5Og m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
123
1
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(132 citation statements)
references
References 25 publications
(32 reference statements)
6
123
1
1
Order By: Relevance
“…Sediment trap studies are known to be subject to inherent "overtrapping" processes that are likely to overestimate actual sediment accumulation rates measured in the sediment cores (Pennington, 1974;Evans, 1994). However, the calcite accumulation rates in the sediment traps are only about 20% higher than the calculated average calcite accumulation rates from the Baldeggersee core and, therefore, are acceptable as being within reasonable error.…”
Section: Sediment Trap Accumulationsmentioning
confidence: 95%
“…Sediment trap studies are known to be subject to inherent "overtrapping" processes that are likely to overestimate actual sediment accumulation rates measured in the sediment cores (Pennington, 1974;Evans, 1994). However, the calcite accumulation rates in the sediment traps are only about 20% higher than the calculated average calcite accumulation rates from the Baldeggersee core and, therefore, are acceptable as being within reasonable error.…”
Section: Sediment Trap Accumulationsmentioning
confidence: 95%
“…Moreover, the great influence of sediment composition, especially grain size, on sediment resuspension has been verified in many lakes (e.g., Somlyody et al 1990). Other studies have shown wind speed and effective lake fetch strongly correlate with sediment resuspension (Douglas et al 2000, van Duin et al 2001, Evans 1994.…”
Section: Introductionmentioning
confidence: 92%
“…A review of field studies in a range of aquatic ecosystems showed that 85% of the resuspendend matter flux to the sediment may be due to resuspended material (Evans, 1994), and that such processes may be an especially dominant cause of turbidity in large shallow lakes (Sheffer, 1998). Although sediment resuspension may be most associated with wave action, bottom-feeding activity may also cause sediment resuspension (Caliman, 2005b).…”
Section: Causes Of Ncl Biodiversitymentioning
confidence: 99%